A novel auxetic sandwich panel for use in structural applications: Fabrication and parametric study. (March 2023) - Park, Eun Byeol; Jeong, Yoon Chang; Kang, Kiju
Abstract: We recently introduced a convex-deformable sandwich panel, composed of two stainless steel face sheets with a 2D auxetic pattern and a 3D-printed double pyramid truss core, selected for the statically and kinematically determinate architecture. As a follow-up to this sandwich panel, the present study proposes a more simplified fabrication of the 3D auxetic panel, which is suitable for general applications. The sandwich panel proposed herein has the same stainless steel face sheets with a 2D auxetic pattern as its predecessor, whereas the truss core is replaced with homogeneous polyurethane foam. This panel has advantages in terms of mass production, cost, structural robustness, and dimensional flexibility. The mechanical behavior of the panel is investigated under tensile and buckling loads, and the result successfully demonstrates the auxetic behavior of the panel under both loads. In addition, the effects of various geometrical parameters and material properties on the auxetic behavior are analyzed using the Taguchi method based on a series of finite element analyses. The ratio of Young's modulus of the face sheets to that of core materials is observed to have the most dominant influence on the auxetic behavior. Graphical Abstract: ga1 Highlights: For structural applications, flexible & thin auxetic sandwich panels are necessary. The sandwich panel is made of stainless steel face-sheets & polyurethane foam core. Under tensile & bending load, auxetic behaviors of panel were successfully realized. The sensitivity of design parameters was investigated by using the Taguchi method. Young's moduli ratio of face sheets to core is the main factor on the auxetic behavior.